Upaya Pemerintah Indonesia Dalam Mengatasi Kebakaran Hutan dan Lahan di Pulang Pisau, Kalimantan Tengah - Hema Yurismi, Afifah; Daniah, Rahmah; Wicaksa, Arif (Department of International Relations, Universitas Mulawarman, 2022)
This study aims to describe the efforts of the Indonesian government in overcoming with forest and land fires in Pulang Pisau, Central Kalimantan. The research method used in compiling this thesis is descriptive type. Data collection techniques using library techniques. The type of data used is primary data in the form of Presidential Regulation of the Republic of Indonesia number 1 of 2016 related to the formation of the BRG and secondary data sourced from research journals, articles and books related to the object of research. In this study, researchers used theory and environmentalism and international cooperation. The results of this study indicate that most of the efforts of the Government of Indonesia in dealing with forest and land fires in Pulang Pisau have gone well, as can be seen from the achievement of the main objectives of the canal blocking project through the FPIC approach which results in the restoration of the peat ecosystem and improving the quality of life of the community. Then, the efforts made are not limited to action plans or policies but concrete actions carried out by district governments, provincial governments, and central governments and in their implementation are not only driven at the government level but also from companies, communities, and supported by foreign partnerships. As for the additional opportunity to be completed, the author sees from year to year still with the same pattern of efforts and no new efforts have been offered by the government. However, the government has used a different approach, namely using the principle of FPIC, which was welcomed by the community.